BRIDGING POLICY AND PRACTICE: MULTI-THEORETICAL PERSPECTIVES ON FOOD SECURITY IN ADAMAWA AND BEYOND (AUN INTERNATIONAL CONFERENCE, 2025)
Food insecurity in Nigeria is not just a pressing issue, but an urgent crisis that poses severe threats to livelihoods, health, and economic well-being. The actions, inactions, and interests of diverse stakeholders drive this crisis. This paper focuses on Adamawa State within the BAY region (Borno, Adamawa, and Yobe) of North-East Nigeria, where persistent insecurity reflects the interplay of behavioral complacency, institutional voids, conflict-related shocks, competing interests, and local contextual dynamics. Despite decades of government policies, international donor interventions, local initiatives, and academic research, the country continues to struggle with the fundamentals of food availability, accessibility, and affordability.In investigating this wicked and complex problem, the study employs a multi-theoretical framework combining Entitlement Theory, Political Ecology, Resilience Theory, and Digital Ecosystem Theory. This approach not only highlights the challenges of fragile value chains, institutional weaknesses, and community-level inaction but also underscores the significant and hopeful transformative potential of digital platforms and grassroots innovations. Drawing on immersive fieldwork, cross-country experiences, and lived realities in East Africa and Asia, the paper argues that top-down interventions alone are grossly inadequate.The analysis emphasizes the importance of micro-level commitments, such as home gardening, water harvesting, hydroponics, and value addition. It also underscores the crucial need for greater practical engagement by Universities, private sector actors, and smallholder farmers.  The study concludes that achieving long-term food security in Nigeria requires localized, technology-enabled, and behaviorally informed strategies that strengthen community resilience while adapting proven practices from other African contexts.